2017
DOI: 10.18203/2319-2003.ijbcp20171677
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparative study of two intubating doses of cis-atracurium during general anaesthesia for gynaecological surgery

Abstract: INTRODUCTIONCisatracurium besilate is a cis-cis isomer (51W89:1R-cis 1'R-cis atracurium), one of the 10 stereoisomers of atracurium that constitutes 15% of the atracurium mixture, an intermediate duration non-depolarising neuromuscular blocking drug. It is about three to four times more potent than atracurium and devoid of cardiovascular side effects in doses of upto 8 times of ED95. The ED95 of cisatracurium is 0.05mg/kg. 1-5The rate limiting step in the degradation of cisatracurium is Hoffmann degradation.(o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It correlates with our study. [7] Amini Shahram et al (2011) studied effects of different doses of cisatracurium on appropriate time for endotracheal intubation and hemodynamic changes during anaesthesia and found that the mean clinical duration of action with 0.15 mg/kg was 44.93±5.40 minutes while with 0.2 mg/kg was 57.03±4.21 minutes, which correlates with our study. [8] Bluestein LS, Stinson LW, et al (1996) reported that increasing the initial dose of cisatracurium (from 0.1 to 0.15 and 0.2mg/kg) increased the mean time of clinically effective duration (45 to 55 and 61 min) respectively, which correlates with our study results.…”
Section: Discussionsupporting
confidence: 90%
“…It correlates with our study. [7] Amini Shahram et al (2011) studied effects of different doses of cisatracurium on appropriate time for endotracheal intubation and hemodynamic changes during anaesthesia and found that the mean clinical duration of action with 0.15 mg/kg was 44.93±5.40 minutes while with 0.2 mg/kg was 57.03±4.21 minutes, which correlates with our study. [8] Bluestein LS, Stinson LW, et al (1996) reported that increasing the initial dose of cisatracurium (from 0.1 to 0.15 and 0.2mg/kg) increased the mean time of clinically effective duration (45 to 55 and 61 min) respectively, which correlates with our study results.…”
Section: Discussionsupporting
confidence: 90%
“…who did not perceive any noteworthy changes in HR too and inferred that the maximum HR changes were small and non-significant. [ 13 14 ] The overall change in HR and MAP in the study was minimal, perhaps attributable to the use of N 2 O, barbiturate, and fentanyl that masked the hemodynamic changes associated with histamine release, making it more difficult to recognize the clinical signs of this phenomenon. El Kasaby et al .…”
Section: Discussionmentioning
confidence: 98%
“…El-kasaby et al, 16 in their study observed that hemodynamic stability for both mean arterial pressure and heart rate was more evident when cisatracurium with higher dosage (4ED 95 and 6ED95) as compared to (2ED 95 dose of atracurium and 2ED95 dose of cisatracurium which was statistically significant (P<0.05) which can be attributed to absence of dose-dependent histamine release in cisatracurium group. Jammar et al, 24 also concluded better hemodynamics with higher dose of (4ED95) cisatracurium compared to the lower dose (3ED95).…”
Section: Hemodynamic Comparisonmentioning
confidence: 94%